Training for caregivers of the elderly and new labour market challenges - ELŻBIETA STRZELECKA (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
Research into the scale of population aging in selected European countries shows that a new resource of caregivers to the elderly should be trained taking account of market needs. The knowledge of demographic trends, determinants arising from healthcare and welfare policies, the care needs of the elderly and the needs of their caregivers, training and education opportunities for the caregivers is a basis for the development and implementation of innovative, pilot courses for both informal and formal caregivers. This article describes chosen factors which have got influence on content and shape of vocational trainings for elderly caregivers and presents effects of pilot trainings for formal and informal caregivers as the part of Nurse Managed Care for Elderly project. Such courses help enhance human capital potential at both local and national levels, which facilitates the development of communities including the sector of „silver” and “white” economy.